(3GfgGV GdeTQhYGJ GdeJYKQI hhbGjJgG ef GdEadGS (B: s (3OQGSI ebGQfI Hjf GdbGfhf GdhVYj hGdabg GdESdGej (B/ s - (3eSYhO jhfS YWhGf YWGs; (3GfhQ eMehO OHhQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2008)
(3GdeTQhYGJ GdeJYKQI gj (B: (3GdJj JhGLg XQhaG YGQVI GKQJ aj fJGFL GYeGdgG (B: (3hdcf dOjgG GecGfjGJ efJLI jecf HhGSWJgG GUdGM eSjQJgG (B: (3hGdfghV ef YKQJgG (B: (3GPG JhGaQJ dgG GdSHd hGdehGQO GdeGdjI(B. (3hGf GfgGV GdeTQhYGJ jYfj (B: (3JMhd GdeTQhYGJ GdeJYKQI Gdj MGdI GdjSQ (B: (3Yf WQjb efM GdCLd (B: (3Gh JNajV GdOjf (B: (3Gh cdjgeG (B: (3hGjLGO eUGOQ LOjOI dJJhjdgGs
(3GWQhMI(B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2008s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B494-536s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdeTQhY GdeJYKQs; (3GdGadGS hGdGYSGQs; (3TQcI GdTNU GdhGMOs; (3GdJhba Yf GdOaYs; (3GfgGV GdeTQhYGJ GdeJYKQIs; (3GdJShjI GdhOjIs; (3GdOjhf GdeJYKQIs; (3GdUdM GdhGbj ef GdGadGSs; (3GdGdjGJ GdJehjdjIs; (3GdJGLjQ GdJehjdjs; (3GdeSFhdjI GdeOfjI hGdLfGFjIs; (3YbO GdSdes; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs